Penerapan Algoritma Gopala Hemachandra Code 2 (GH2(N)) Untuk Kompresi Record pada Database MYSQL - Diana Novita (Bulletin of Information System Research, 2024)
In the rapid development of technology, a data storage medium has become an obligation that must be owned by every human being who is always in contact with computers, be it internal data storage or external data storage. Similarly, a database has become a basic need for every individual or organization to carry out a computerized activity. A database is a collection of text data that forms a file that is interconnected in a certain way to form new data or new information. From these problems, a technique was found in order to solve all the problems found previously. The technique is called the compression technique. is the process of converting the original (raw) data into another data stream with a different format that has a smaller size or the process of converting a set of data into code form with the aim of saving storage space. In this case the author uses in compression is the Gopala-Hemachandra Code 2 (GH-2(n)) algorithm for file record compression. So from this research will be obtained what percentage of the data before the compression process is done with the one that has been decompressed. So that users can also save more storage space without losing information, besides that the time used in the transmission process will be less.